2016
DOI: 10.1177/0022167816668114
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of a Spiritual Emergency Experience Into a Client’s Worldview: A Grounded Theory

Abstract: This study is focused on the process of constructing the meaning of a spiritual emergency experience. In the context of this study, spiritual emergency is understood as an experience of psychotic nature, defined by criteria such as good preepisode functioning, nonordinary states of consciousness, awareness of the intrapsychic nature of the process, or preserved ability to cooperate. In-depth interviews with 13 participants who experienced an episode of spiritual emergency were analyzed using the grounded theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Qualitative research points to the importance of the interpersonal context when integrating out-of-the-ordinary experiences into a person's life, including the opinions of significant others and spiritual or medical professionals (Heriot-Maitland et al, 2012;Sedla´kova´& Ř iha´cˇek, 2016). It is therefore important not to apply fixed labels to such experiences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research points to the importance of the interpersonal context when integrating out-of-the-ordinary experiences into a person's life, including the opinions of significant others and spiritual or medical professionals (Heriot-Maitland et al, 2012;Sedla´kova´& Ř iha´cˇek, 2016). It is therefore important not to apply fixed labels to such experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Research points to the importance of the interpersonal contextawareness of the other's views as pathologising or normalisingwhen integrating out of ordinary experiences into one's life, including the opinions of significant others and professionals that people seek help from (Heriot-Maitland et al, 2012;Sedláková & Řiháček, 2016). Therefore it is important not to rush into applying labels to experiences that are less understood phenomena.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Emergent themes reflected a variety of divine struggles: difficulties developing close relationships with God, feeling emotionally distant from God, negative feelings toward God, and emotional insecurity in relationships with God. Finally, a study of 13 participants used grounded theory to analyze semistructured interviews focusing on a spiritual emergency, a non-ordinary state of consciousness that centers on r/s themes and commonly involves sensory, perceptual, and emotional changes that can be profoundly transformative and distressing (Sedláková and Řiháček 2019). Results showed that some participants mitigated the meaning of the spiritual emergency, whereas others struggled to make meaning from their experiences and were eventually able to incorporate the spiritual emergency into their identities.…”
Section: Summary Of Previous Researchmentioning
confidence: 99%